Enhancing 21st-century teaching competencies: The key role of digital literacy in connecting pre-service teachers' TPACK - Aslan, Serkan; Alanoglu, Muslim; Karabatak, Songuel (Sage Publications Ltd, 2025)
This research examines the direct effects of pre-service teachers' Technological Pedagogical Content Knowledge (TPACK) levels on the instruction of twenty-first-century teaching skills and the indirect effects mediated by digital literacy. The research was conducted using a cross-sectional survey design and involved 468 fourth-year students from the education faculties of two universities in Turkey. Structural equation modeling was employed to analyze the data. The results indicate that TPACK has both a direct and an indirect effect, mediated by digital literacy, on pre-service teachers' competencies in twenty-first-century teaching skills. It was found that digital literacy partially mediates this relationship. The analysis revealed that the direct effect of TPACK on competencies in teaching twenty-first-century skills was beta = 0.39 (p < 0.01), while the indirect effect mediated by digital literacy was calculated as beta = 0.28 (p < 0.01). Digital literacy accounts for 56% of the total effect of TPACK on teaching competencies. These findings underscore the significant contribution of both TPACK and digital literacy in pre-service teachers' effective instruction of twenty-first-century skills. Based on these results, the study offers several recommendations for teacher education processes.
Keywords: Technological pedagogical content knowledge; digital literacy; twenty-first-century teaching skills; pre-service teachers